Calix[2]triazole[2]arenes; A Class of Hybrid Heterocalixarenes. Issue 21 (5th June 2013) - Cho, Jihee; Lee, Seokwoo; Hwang, Soonho; Kim, Sang Hoon; Kim, Jong Seung; Kim, Sanghee
Abstract: A series of calix[2]triazole[2]arenes, which are members of the heterocalixarene family, were generated by copper(I)‐catalyzed Huisgen reaction in a one‐pot synthesis. Their various conformational structures and physical properties were characterized by a computational, NMR spectroscopic, and X‐ray structural investigation. Among six conformations, the 1, 2‐alternate conformation was found to be the most stable due to two intramolecular hydrogen bonds between the phenolic hydroxyl group and the triazole nitrogen atom. Abstract : A series of calix[2]triazole[2]arenes, members of the heterocalixarene family, were synthesized and their various conformational structures were characterized on the basis of their X‐ray crystal structures and NMR spectra.